2013
DOI: 10.1111/jog.12102
|View full text |Cite
|
Sign up to set email alerts
|

Optimal timing of prophylactic antibiotic for cesarean delivery: A randomized comparative study

Abstract: Administration of prophylactic antibiotic at 30-60 min before skin incision resulted in better maternal outcome when infectious morbidity and postoperative hospital stay were concerned, without influencing the neonatal outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 40 publications
6
10
0
Order By: Relevance
“…These results are consistent with the results of studies conducted [12][13][14][15] There was also no statistically significant difference between groups found in indication for LSCS in emergency (P=0.0822) and elective (P=0.0813). Similar study was done by Thigpen et al previously showing no significant differences in indication for LSCS (P=0.54).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These results are consistent with the results of studies conducted [12][13][14][15] There was also no statistically significant difference between groups found in indication for LSCS in emergency (P=0.0822) and elective (P=0.0813). Similar study was done by Thigpen et al previously showing no significant differences in indication for LSCS (P=0.54).…”
Section: Discussionsupporting
confidence: 83%
“…23,28 Present study revealed neonatal morbidities like neonatal sepsis (p=0.0693), neonatal fever (P=0.0656), neonatal poor feeding (P=0.0655), birth asphyxia (0.0620), SNCU admission (P=0.0766) had no significant differences in both group; results were similar in the previous studies also as mentioned in above paragraph. Mean hospital stay of mothers was significantly less in study group (P=0.0001) which is consistent with other studies as of Smaill F et al and Bhattarjee N et al 14,17 The sample size was medium but significant. Pharmacokinetics of antibiotic in individual patient could not be compared.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We included 18 RCTs comparing the application of prophylactic antibiotics before vs. after cord clamping (13,(17)(18)(19)(20)(21)(22)(23)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). The studies were conducted in the USA (17,20,29,(32)(33)(34)(35), Turkey (37), Austria (36), India (28,30), Iran (18,21), Egypt (31), Tunisia (19), Sudan (22), Italy (23) and China (13). The indication for the cesarean section, number of randomized women in treatment groups, antibiotic class, agent and dosing scheme of the administered antibiotic(s) and the actual time when the antibiotic(s) were given, are presented in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…The indication for the cesarean section, number of randomized women in treatment groups, antibiotic class, agent and dosing scheme of the administered antibiotic(s) and the actual time when the antibiotic(s) were given, are presented in Table S1. In brief, 13 studies included women with elective cesarean section solely (13,(17)(18)(19)(20)22,(29)(30)(31)(32)(33)36,37), two studies reported that more than 75% of women received elective cesarean section (21,28), and three studies were focused on non-elective cesarean section (23,34,35). The majority of studies administered a first-generation cephalosporin (cefazolin 1 g, cefazolin 2 g or cefathiamidin 2 g) (13,18,19,21,29,(31)(32)(33)(34)(35)(36)(37).…”
Section: Resultsmentioning
confidence: 99%